Rs37972 and rs37973 single-nucleotide polymorphisms in the glucocorticoid-inducible 1 gene are not associated with asthma risk in a Saudi Arabian population. (March 2015) - Al-Muhsen, Saleh; Vazquez-Tello, Alejandro; Jamhawi, Amer; Al-Dosari, Mohamed S.; Mahboub, Bassam; Iqbal, Nizam; Temsah, Mohamed Hani; Al-Eyadhy, Ayman; Alharbi, Nasser; Halwani, Rabih
Abstract Objective: Rs37972 and rs37973 variants in the glucocorticoid-induced transcript 1 gene have been associated with inhaled glucocorticosteroid responsiveness in asthmatics; however, some discrepancies have been also reported. This study aims to determine whether rs37972 and rs37973 SNPs are associated with asthma risk in Saudi Arabian asthmatics. Methods: Two-hundred seventy-one diagnosed asthmatics (3–65 years old) and 387 healthy control subjects of equivalent age were recruited. DNA from peripheral blood was purified, and genotyping of rs37972 and rs37973 SNPs was performed by PCR amplification of segments of interest, followed by Sanger sequencing. Results: The global frequencies of the minor (risk) alleles were 28% ("T" allele, rs37972) and 30% ("G" allele, rs37973). Yates-corrected Chi-square (χ2) tests revealed significant differences between asthmatic and healthy groups, in allele frequencies for rs37973 SNP only (χ2 = 3.98, Yates' p value = 0.046). Regarding genotype frequencies, a significant difference between asthmatic and healthy groups was observed for variant rs37972 only (χ2 = 8.19, Yates' p value = 0.016). To determine a possible association of the minor "T" and "G" alleles with asthma, both the recessive and dominant genetic models were tested. For rs37973, none of the genotypes were significantly associated with asthma. Concerning rs37972, the dominant model (C/T + T/T versus C/C) indicated a significant "protective" association with asthma, in which C/T + T/T individuals had lower odds of being asthmatics than C/C individuals (OR = 0.67; 95% CI = 0.48–0.94; p = 0.019*). Conclusions: The minor alleles "T" and "G" of rs37972 and rs37973 SNPs, respectively, were not significantly associated with increased asthma risk in asthma patients from Saudi Arabia.